Dissecting short-sale performance: Evidence from large position disclosures - Stephan Jank; Esad Smajlbegovic (University of Cologne, Centre for Financial Research (CFR), 2015)
Short sellers are perceived as informed, sophisticated investors. Yet little is known about their actual performance and trading strategies. Using a novel, hand-collected data set of daily position disclosures in Europe, we identify the entry, change, and exit dates of large short-sale positions for a wide cross section of stocks and investors. We find that hedge funds, the predominant investor group, generate an annualized Fama and French (1993) risk-adjusted return of about 5.5%, outperforming other investors. Evidence indicates that hedge funds act as arbitrageurs, generating their returns by trading on the mispricing-related factors, e.g. momentum, betting-against-beta, and quality-minus-junk. In the cross section of hedge funds, local, diversified, and active funds outperform their counterparts. On the position level, we document a first-mover advantage. The profitability of short sales also varies significantly with investors' holding period, location, and industry experience.
Keywords: G14; G15; G23; 330; Short-sale performance; Anomalies; Hedge funds; Fund attributes